Multiple barriers to participation for people with psychosocial disability in Dehradun district, North India: a cross-sectional study. Issue 2 (27th February 2018) - Mathias, Kaaren; Pant, Hira; Marella, Manju; Singh, Lawrence; Murthy, GVS; Grills, Nathan
Abstract : Objectives: This study used a population-based cross-sectional survey to describe the prevalence of psychosocial disability and unmet need for access to services in North India. Setting: This study was conducted in Dehradun district, Uttarakhand, in 2014. Participants: A population-based sample of 2441 people over the age of 18 years. Primary outcome measures: The Rapid Assessment of Disability survey tool identified people with disability and used an adapted version of the Kessler scale to identify those with psychosocial disability. It additionally collected information on socioeconomic variables, access to community services and barriers to participation. Prevalence of psychosocial disability and unmet needs and descriptions of barriers to services were calculated, and multivariable logistic regression was used to assess associations between risk factors and psychosocial disability. Results: Prevalence of psychosocial disability was 4.8% and 75% of participants with psychological distress also reported comorbid functional impairments. Adjusted ORs for depression of more than two were found for people who were unschooled, unemployed and of moderate or poor socioeconomic status. The unmet need for access to services was significantly higher in every domain for people with psychosocial disability and was more than 25% in the areas of employment, health service access and community consultation. People with psychosocial disability encountered greater barriers in each domain compared with controls. Conclusions: People who are poor, uneducated and unemployed are two to four times more likely to have psychosocial disability in Dehradun district. They face unmet needs in accessing community services and perceive negative social attitudes, lack of physical accessibility and lack of information as barriers limiting their participation. Social policy must increase access to education and reduce poverty but additionally ensure action is taken in all community services to increase information, physical accessibility and social inclusion of people with psychosocial and other forms of disability.